2009
DOI: 10.1007/s12010-009-8673-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Collagenase from Bacillus pumilus Col-J

Abstract: The collagenase, produced extracellular by Bacillus pumilus Col-J, was purified by ammonium sulfate precipitation followed by two gel filtrations, involving Sephadex G-100 column and Sepharose Fast Flow column. Purified collagenase has a 31.53-fold increase in specific activity of 87.33 U/mg and 7.00% recovery. The collagenase has a relative molecular weight of 58.64 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The optimal temperature for the enzyme reaction was 45 degrees C. More than 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 26 publications
4
46
1
2
Order By: Relevance
“…The enzyme was stable between pH 6.0 and 10.0 during the first 8 h, but after 28 h its stability was restricted to a pH range from 7.0 (50.7%) to 9.0 (75.1%). In accordance with Wu et al [6], collagenase from B. pumilus is stable between pH 6.5 and 8, the enzyme retained above 84% of full activity after 30 min. By retaining more than 80% of its stability at pH 8 and 9, the enzyme described in the present work proved to be very stable in comparison with the collagenase produced by other microorganisms.…”
Section: Effect Of Ph On Collagenolytic Activity and Stabilitysupporting
confidence: 89%
See 4 more Smart Citations
“…The enzyme was stable between pH 6.0 and 10.0 during the first 8 h, but after 28 h its stability was restricted to a pH range from 7.0 (50.7%) to 9.0 (75.1%). In accordance with Wu et al [6], collagenase from B. pumilus is stable between pH 6.5 and 8, the enzyme retained above 84% of full activity after 30 min. By retaining more than 80% of its stability at pH 8 and 9, the enzyme described in the present work proved to be very stable in comparison with the collagenase produced by other microorganisms.…”
Section: Effect Of Ph On Collagenolytic Activity and Stabilitysupporting
confidence: 89%
“…Comparing results of temperature assays, Wu et al [6] found for B. pumilus collagenase an optimum temperature of 45 °C, and with heating, the collagenase retained above 50% activity at 70 °C. Baehaki et al [35] assayed the collagenase activity between 30 and 90 °C, being observed an increase in enzymatic activity between 30 and 50 °C, with a strong reduction occurring above 60 °C.…”
Section: Effect Of Temperature On Collagenolytic Activity and Stabilitymentioning
confidence: 99%
See 3 more Smart Citations